Central sensitization in breast cancer survivors. Issue 2 (2nd April 2018) - Cuesta‐Vargas, Antonio I.; Roldan‐Jimenez, Cristina; Pajares, Bella; Alba, Emilio; ,
Abstract : The goal of this study was to study central sensitization (CS)‐related symptoms in breast cancer (BC) survivors and to find if there are differences in clinical and functional variables. In this cross‐sectional study, 25 women aged between 32 and 69 years participated. CS pain was measured with the Central Sensitization Inventory (CSI). Forty points was considered the cutoff value. Cancer‐related fatigue (CRF), Quality of life, functional capacity, and handgrip strength (HGS) was assessed. A 60% of BC survivors showed a CSI score from 0 to 40, while the rest 40% of women had a score higher than 40, CSI scores being 38.35 ± 14.54 points in the whole sample. Significant differences were found in functional capacity, CRF and QoL ( p  < .011). However, there were no differences in HGS ( p  = .089). This is the first study to report BC survivors CS‐related symptoms. The high CS‐related symptoms group showed differences in some symptoms and functional capacity in this population. Future research including a wider sample and more variables related to pain should be carried out.